Quality of Service (QoS) Pada Jaringan Wi-Fi (Wireless Fidelity) FKIP UNTIRTA Menggunakan Software Wireshark - Ratnasari Ratnasari; Fernando Juliansyah; Gera Nugraha; Dede Wirta; Didik Aribowo (Politeknik Kampar, 2025)
Wi-Fi (Wireless Fidelity) networks have become vital infrastructure in the era of modern wireless communications. With the rapid development of technology, monitoring and analyzing Wi-Fi networks has become increasingly important to ensure optimal performance and guaranteed security. Wireshark software has become one of the most popular and reliable tools in analyzing computer networks, including Wi-Fi networks. Wireshark is a very popular and powerful open source network analysis software. Originally known as Ethereum, Wireshark was developed by a team of volunteers and released under the GNU General Public License (GPL). The software can run on multiple platforms, including Windows, macOS, and Linux, making it a flexible tool for network analysis. The method used shows how to solve an analysis or analysis of a problem. This method section uses a literature study which is packaged briefly, clearly and concisely, so that it can be understood well. Another method used is to carry out simulation practices on Wireshark software to get results from a network. This abstract discusses the use of Wireshark in the context of Wi-Fi networks, covering basic Wi-Fi network concepts, monitoring and analysis methods, and security applications. Through careful monitoring and analysis with Wireshark, users can identify network performance issues, detect security threats, and optimize use of their Wi-Fi network. This abstract provides a comprehensive overview of Wireshark's role in understanding and effectively managing Wi-Fi networks.